Omega-3 Fatty Acids and Renal Health: Mechanisms, Protective Effects and Clinical Implications – A Narrative Review - Bogdan , Klaudia; Jankowski, Mikołaj; Janicka, Urszula; Ciepluch, Natalia; Słomiński, Szymon; Toczek, Wiktoria; Olszówka, Magdalena; Dziugieł, Sonia (Quality in Sport, 2026)
Background: Chronic kidney disease (CKD) is a major global health problem associated with increased cardiovascular risk, progressive renal function decline, and high mortality. Despite advances in pharmacological therapy, disease progression often persists, highlighting the need for supportive, lifestyle-based interventions. Omega-3 polyunsaturated fatty acids (PUFAs) have gained interest in nephrology due to their anti-inflammatory, anti-oxidative, and endothelial-protective properties. Aim of the study: This narrative review aimed to summarize current evidence on the role of omega-3 PUFAs, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), in renal health, with emphasis on mechanistic pathways and clinical implications in chronic kidney disease and inflammation-related renal injury. Materials and methods: A narrative literature review was conducted using PubMed, Scopus, and Google Scholar. Publications from 2020–2025 were prioritized, including randomized controlled trials, systematic reviews, meta-analyses, and experimental studies. Search terms included omega-3 fatty acids, EPA, DHA, chronic kidney disease, proteinuria, renal inflammation, and fibrosis. Current stage of knowledge: Omega-3 fatty acids exert pleiotropic effects relevant to renal protection, including modulation of inflammatory signaling, oxidative stress, mitochondrial dysfunction, endothelial function, and fibrotic pathways. Clinical data suggest modest but consistent reductions in proteinuria, particularly in IgA nephropathy and early-stage CKD, while effects on long-term renal function decline remain inconsistent. Conclusions: Omega-3 fatty acids may offer supportive renoprotective benefits, especially in proteinuric and inflammation-mediated kidney diseases. They should be considered an adjunct to established therapies. Further long-term studies are needed to identify optimal dosing and patient populations most likely to benefit.